Pengaruh Rekomendasi Penasehat Keuangan dan Literasi Keuangan Terhadap Niat Berinvestasi Studi Empiris Mahasiswa di Kota Medan - Jodihartandi Jodihartandi; Marliyah Marliyah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to find and analyze the effect of financial advisor recommendations and financial literacy on student investor intentions in Medan. This research is a quantitative research with an explanatory research model, with primary data. Data collection techniques using a questionnaire. The data analysis technique is statistical analysis with the help of SPSS 22 for windows software. The results of the study found that financial advisor recommendations had a positive effect on investor intentions and financial literacy had no effect on investor intentions. The results of the calculation of the coefficient of determination of the perception of financial advisor recommendations, financial literacy has an influence of 32% on student investor intentions and while 68% is influenced by other factors outside of this study.